Representasi Kecantikan dalam Iklan Scarlett Whitening Idol Korea TWICE - Adelia Rahma Putri; Arizal Mutahir; Rili Windiasih (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2026)
Globalization and the massive influence of Korean popular culture have shifted the construction of women's beauty standards in Indonesia, including the marketing strategies of local cosmetic products. This study aims to analyze the representation of women's beauty standards and the ideological construction in the local brand advertisement Scarlett Whitening, specifically the